Penilaian Sistematik Berbasis Ecological Linguistics dalam Pembelajaran Bahasa Arab - Nazilatil Maghviroh; Azisi (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2021)
The ecological approach in language teaching arises from the need to understand language within its social, cultural, and physical contexts, beyond mere linguistic aspects. This article provides a systematic literature review on the application of the ecological approach in teaching Arabic language communication, aiming to assess current practices and offer directions for future research. The study finds that the ecological approach enhances contextual understanding and student engagement through authentic learning environments. Emphasis on social interaction, cultural contextualization, and technological support are key elements in this approach. Despite its many benefits, the implementation of this approach faces challenges, particularly in cultural adaptation and resource limitations. The article recommends further development in teacher training and technology integration to enrich the holistic Arabic language learning experience.